Smear layer removal efficacy of pineapple core extract bromelain as a candidate of novel endodontic irrigant - A scanning electron microscopic study - Ketut Suardita; Muhammad Nur Alfarizi; Achmad Junaidi; Ige Frameski Radila Muga; Nur Dianawati; Daradhasih Bestari Santiaji; Masaru Ohara (Conservative Dentistry Journal, 2026)
Background: Removing the smear layer is a critical step in root canal treatment. A 17% ethylenediaminetetra acetic acid (EDTA) solution is frequently utilized as an irrigation solution; however, EDTA can cause excessive loss of calcium ions from the root dentin and may reduce dentin hardness. The potential effectiveness of bromelain in removing the smear layer within the root canal walls has not yet been extensively studied. Purpose: This research intended to assess the effectiveness of bromelain derived from a pineapple core in its capacity to eliminate the smear layer after root canal treatment Methods: Twenty one mandibular premolar were instrumented and randomly assigned to seven groups according to the irrigation protocol: Group I (aquadest), Group II (17% EDTA), Group III (12.5% bromelain), Group IV (25% bromelain), Group V (50% bromelain), Group VI (75% bromelain), and Group VII (100% bromelain). Smear layer removal was evaluated using SEM. A Kruskal Wallis test was was used for intragroup comparisons and a Mann-Whitney U test for intergroup comparisons, where a p-value < 0.05 was considered significant. Results: Notable variations were noted between the distilled water group and those treated with 25% and 50% bromelain. A notable difference was evident between the 17% EDTA group and those given bromelain at 12.5%, 75%, and 100% concentrations, while no significant difference was found with the groups receiving 25% and 50% concentrations. Conclusion: Bromelain derived from pineapple core extract effectively eliminates the smear layer from the root canal.